UJI TEKNIS BIOGAS DARI BAHAN BAKU FESES SAPI DI DESA TOTABUAN KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW - Batin E. Tuwuilu; David P. Rumambi; Ruland A. Rantung; Herry F. Pinatik (COCOS, 2014)
ABSTRACTEnergy is a crucial global issue. Demand for energy increases every year. According todata collected by the Ministry of Energy and Mineral Resources (2006) Indonesia’s oilsupply amounts to a mere 9 billion barrels, which will run out with continued consumption.To decrease dependency on fossil fuels, the government has issued Peraturan PresidenRepublik Indonesia number 5 year 2006 about National Energy Policies to developalternative renewable energy resources. Energy experts around the world are now researchingand developing renewable energy, one of which is biogas. This research is done in Totabuanvillage, district of Lolak, Bolaang Mongondow regency, using experimental methods withdescriptive analysis of the formation of biogas using biodigester technology with a permanent12 m3 dome-type reactor. Biogas started forming on the 9th day, up to the 26th day, with 12m3 of raw materials, which is a 1:1 mix of cow feces with water (6 m3 cow feces and 6 m3water), and yielded 4,68 m3 of biogas that can be used to cook for 12,3 hours. Each 1 m3 ofbiogas can be used to cook for 2,63 hours. Biogas yield is 39%Keywords: Energy, Renewable, Biodigester, Biogas.